TOTAL ANTOSIANIN EKSTRAK BUAH SALAM DAN KORELASINYA DENGAN KAPASITAS ANTI PEROKSIDASI PADA SISTEM LINOELAT - Setyaningrum Ariviani (AGROINTEK, 2010)
Dark red colored salam (Syzygium polyanthum [Wight.] Walp) fruits was expected contain of anthocyanin compounds. Previous research results have shown that anthocyanins from edible fruits were effective antioxidants. Antioxidative properties of anthocyanins arise from their high reactivity as hydrogen or electron donors, and from the ability of the polyphenol-derived radicals to stabilize and delocalize the unpaired electron, and from their ability to chelate transition metal ion. This research aims to determine total anthocyanin content of salam fruits extracted with different solvent proportion and their correlation to the anti peroxidation capacity on linoleic system. Results of this research indicated total anthocyanin content of salam fruits exctract increased along to solvent proportion raised. The anti peroxidation capacity showed no correlation with the total anthocyanin content (R 0.283, P 0.644)